AEROBIC EXERCISE PROGRAMS AND THEIR BENEFITS IN BREAST CANCER: A SYSTEMATIC REVIEW (Cuestiones de Fisioterapia, 2019)
Introduction: nowadays, the aerobic exercise and the exercise program benefits neoadjuvant and adjuvant set-ting in the breast cancer treatment are being investigated. Objective: analyze the available scientific evidence on the benefits of the aerobic exercise and the best modalities for women with breast cancer. Material and method: review of the scientific literature has been carried out in the databases Cinhal, Medline, PubMed and Scopus, using the descriptor MeSH: Breast Neoplasms, and the free term aerobic exercise. Results: after applying the exclusion and inclusion criteria 14 articles were analyzed. 42.86 % of the researchers studied exclusively aerobic exercise programs, while the remaining 57.14 % also added strengthening and/or resistance training. Conclusions:Aerobic exercise is a safe and effective exercise modality, and it has positive repercussions on such common breast cancer symptoms as fatigue, loss of aerobic capacity, strengthening, endurance, increase in body mass index, weight, pain, quality of life and quality of sleep.